2021
DOI: 10.1101/2021.06.11.448119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Basis for Cytoplasmic Dynein-1 Regulation by Lis1

Abstract: The lissencephaly 1 gene, LIS1, is mutated in patients with the neurodevelopmental disease lissencephaly. The Lis1 protein is conserved from fungi to mammals and is a key regulator of cytoplasmic dynein-1, the major minus-end-directed microtubule motor in many eukaryotes. Lis1 is the only dynein regulator that binds directly to dynein's motor domain, and by doing so alters dynein's mechanochemistry. Lis1 is required for the formation of fully active dynein complexes, which also contain essential cofactors: dyn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 78 publications
(139 reference statements)
9
21
0
Order By: Relevance
“…Consistent with previous reports 13, 15, 16 , these results indicate that Lis1 binding increases the microtubule binding affinity of dynein. Mutagenesis of the Lis1 interaction site on dynein’s stalk in dynein EQN did not recover dynein velocity, demonstrating that Lis1’s interaction with the AAA+ ring is primarily responsible for slower movement 15, 16 . These results are consistent with a model in which Lis1 binding to the AAA+ ring prevents nucleotide-induced rigid body motions of the AAA+ subunits and traps the AAA+ ring in the high microtubule affinity conformation 15 , resulting in a slower velocity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports 13, 15, 16 , these results indicate that Lis1 binding increases the microtubule binding affinity of dynein. Mutagenesis of the Lis1 interaction site on dynein’s stalk in dynein EQN did not recover dynein velocity, demonstrating that Lis1’s interaction with the AAA+ ring is primarily responsible for slower movement 15, 16 . These results are consistent with a model in which Lis1 binding to the AAA+ ring prevents nucleotide-induced rigid body motions of the AAA+ subunits and traps the AAA+ ring in the high microtubule affinity conformation 15 , resulting in a slower velocity.…”
Section: Discussionsupporting
confidence: 93%
“…Because Lis1 increases the microtubule affinity of dynein (Fig. 1) 13,15,16 , we also tested whether Lis1 binding slows dynein motility by altering the detachment kinetics of dynein from the microtubule. Nucleotide hydrolysis in dynein's AAA+ ring controls its microtubule affinity by altering the registry of the stalk coiled coils [39][40][41] .…”
Section: Lis1 Reduces the Asymmetry In Force-induced Detachment Of Dy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that a myriad of complex Lis1-dynein interactions tailor the motor’s functionality. In support of this, the Lis1 stalk is dispensable for microtubule plus-end localisation but necessary for cortical and spindle pole body association in yeast (Gillies et al, 2022). Our data establishes Lis1-5A as another separation-of-function mutant (and the first in humans) that may be a useful tool to further our understanding of Lis1-mediated dynein regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Precisely how mutation of these five residues alter Lis1-dynein binding and/or mechanochemistry is unclear. During preparation of this manuscript the high-resolution structure of the yeast Lis1(Pac1)-dynein complex was reported, which revealed additional dynein contacts in the Lis1 propeller and detailed how the Lis1 stalk interacts with dynein (Gillies et al, 2022). Moreover, this study found that human Lis1 likely contains additional contacts required for dynein regulation.…”
Section: Discussionmentioning
confidence: 99%